2017
DOI: 10.3390/ijms18040705
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in Legume-Rhizobia Symbioses

Abstract: Most species in the Leguminosae (legume family) can fix atmospheric nitrogen (N2) via symbiotic bacteria (rhizobia) in root nodules. Here, the literature on legume-rhizobia symbioses in field soils was reviewed and genotypically characterised rhizobia related to the taxonomy of the legumes from which they were isolated. The Leguminosae was divided into three sub-families, the Caesalpinioideae, Mimosoideae and Papilionoideae. Bradyrhizobium spp. were the exclusive rhizobial symbionts of species in the Caesalpin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(168 citation statements)
references
References 320 publications
10
133
0
4
Order By: Relevance
“…Thus, extrachromosomal genetic elements, and changes in gene expression (López‐Gómez, Palma, & Lluch, ), can contribute to adaptive mechanisms and the survival of rhizobia in saline soils. These suggestions are supported by the findings of Andrew and Andrew () who showed that lateral transfer of symbiosis‐specific genes within rhizobia genera is an important mechanism allowing legumes to form a symbiosis with rhizobia adapted to particular soils.…”
Section: Insight Into Mechanisms Regulating Salt Stress Tolerance In supporting
confidence: 64%
“…Thus, extrachromosomal genetic elements, and changes in gene expression (López‐Gómez, Palma, & Lluch, ), can contribute to adaptive mechanisms and the survival of rhizobia in saline soils. These suggestions are supported by the findings of Andrew and Andrew () who showed that lateral transfer of symbiosis‐specific genes within rhizobia genera is an important mechanism allowing legumes to form a symbiosis with rhizobia adapted to particular soils.…”
Section: Insight Into Mechanisms Regulating Salt Stress Tolerance In supporting
confidence: 64%
“…In summary, lateral gene transfer of nod and nif genes not only allowed non-Rhizobiaceae (albeit Rhizobiales) species to establish highly specific nitrogen-fixing symbioses with legumes, but these strains also are likely to have genes for plant growth-promoting (PGP) traits that are lacking in classical rhizobia (Andrews and Andrews 2017).…”
Section: Rhizobial and Nonrhizobial Bacteria That Fix Nitrogen And Nomentioning
confidence: 99%
“…Although European, African and American species of Lupinus are generally considered to be nodulated by slowgrowing rhizobia affiliated to different Bradyrhizobium lineages (see Andrews and Andrews 2017 The ability of Microvirga to nodulate lupines may be related to the soil physicochemical properties where they grow. It is known that biotic, for example, the composition and diversity of the microbial community, and abiotic factors, such as salinity, pH, altitude, nutrient availability, etc., play an important role in the interactions between the two partners (Thrall et al 2011;Lemaire et al 2015Lemaire et al , 2016Wang et al 2017;de Castro-Pires et al 2018).…”
Section: Discussionmentioning
confidence: 99%